Behavioral Training of High-Functioning Autistic Children by Music Education of Occupational Therapy - Ting Xia; Zongrun Li (Occupational Therapy International)
Autistic children, also known as “children from the stars”, have been discovered for more than half a century, but there is still no unified conclusion on the diagnosis, causes, manifestations, and education of autism. The current theory and practice suggest that there is a need to improve the treatment and education of these children. According to existing theories and practices, most autistic children show a special interest in music, and music is very effective in the treatment of autistic children, and through musical activities, children with autism can improve their language, social and emotional, cognitive, and sensorimotor development. In this paper, we record and observe the music classes of children with autism. We select two classes with a total of seven children with autism as the observation subjects in the music classes, record the changes in various aspects and behavioral performance of these seven children with autism in the music activities, and analyze and summarize them. The main purpose of this study is to analyze and summarize how the three major music teaching methods are implemented in the music classroom for autistic children and how they can help autistic children with different characteristics. In the end, we summarize the main problems of music teaching for autistic children found in practice and try to make some suggestions, hoping to provide reference for scholars who study music education for autistic children. The music teaching activities were effective in improving the children’s joint attention, movement imitation, rhythm imitation, and cooperation ability, and all three children improved to varying degrees, fulfilling the goals of the teaching activities. The behavioral analysis of the three children during the teaching activities showed that the three children improved their ability to sit comfortably, awareness, musical ability, and rule awareness and reduced inappropriate behaviors and bad emotions, which proved that music education could improve the social and cognitive skills of the children.